416 Polyclonal antibody preparations from avian origin increase mean ruminal pH and reduce rectal temperature of beef steers during transition from forage to high-grain diets. (5th December 2019) - Silva, Gleise M; Podversich, Federico; Santos, Erick R S; Schulmeister, Tessa M; Sanford, Carla D; Luna, Ana C G; Barreneche, Gonzalo; Elejalde, J Sebastian C; DiLorenzo, Nicolas
Abstract: This study investigated the effects of feeding an avian-derived polyclonal antibody preparation (PAP; CAMAS, Inc.) against Streptococcus bovis, Fusobacterium necrophorum, and lipopolysaccharides (40, 35, and 25% of the preparation, respectively) on dry matter intake (DMI), mean ruminal pH (pH), and rectal temperature (RT) of beef steers during a 21-d step-up adaptation to a high-grain diet. Eight ruminally cannulated Angus crossbred beef steers (658 ± 79 kg of BW) were randomly assigned in a crossover design to be transitioned from a diet containing bermudagrass hay [Cynodon dactylon (L.) Pers.] ad libitum plus 0.45 kg/d of molasses with 0 (CON) or 3 g of PAP (PAP) to a high-grain diet. Transition consisted of three 7-d steps of increased inclusion of cracked corn (35, 60, and 80% of the diet DM for STEP1, STEP2, and STEP3, respectively). On each transition d and 7 d after STEP3 (STEP3-7d), ruminal pH and RT were measured every 3 h for 24 h and feed intake was recorded daily throughout the study using the GrowSafe feed intake monitoring system. Feed intake was not influenced by PAP on transition days (P ≥ 0.44) or during the wk each transition diet was offered (P ≥ 0.57). However, DMI linearly decreased, whereas RT increased from STEP1 to STEP3 (P < 0.01). Steers receiving PAP in STEP2 had reduced RT (P = 0.05). Additionally, steers receiving PAP on STEP3 had greater ruminal pH (P = 0.03), nevertheless, pH was similar between treatments in STEP3-7d (P = 0.39). Feeding 3 g of polyclonal antibody preparations against Streptococcus bovis, Fusobacterium necrophorum, and lipopolysaccharides in a 21-d step-up adaptation to high-grain diets may stabilize ruminal pH and reduce rectal temperature of beef steers. Future studies should characterize the effects of PAP on immune response to elucidate potential modes of action of these feed additives.